MORPHOLOGY OF OVARIES IN RATS BORN UNDER HYPOTHERIOSIS CONDITIONS - ZIEEVA G.P. (Scholar Express Journals, 2024)
Morphological changes in the dynamics of postnatal ontogenesis of ovaries were studied in postnatal ontogenesis of ovaries of offspring born from rat mothers with hypothyroidism under experimental conditions. It was found that all morphofunctional components of the ovaries of the experimental group lag behind in the development of all morphofunctional components of the ovaries of the control group compared to rats of the generation, the ratio of the cortex and medulla layers and the development of follicles were preserved in a hypercellular form for 14-30 days, the vessels increased in size and branching, it was found that the mesenchymal tissue in the medulla of the ovaries continued to increase
Keywords: morphology; mother rat; hypothyroidism